Are We Richer Than Our Parents Were? Absolute Income Mobility in Australia - Tomas Kennedy; Peter Siminski (Institute of Labor Economics (IZA), 2021)
We conduct the first dedicated study of absolute income mobility in Australia, for 1950-2019. About two-thirds of 30-34 year-olds have higher real incomes than their parents did at the same age, and this has been stable for 25 years. This is among the highest levels of absolute mobility in the world. Nevertheless, mobility was considerably higher for baby-boomers (over 80% had higher incomes than their parents). About two-thirds of this decline in mobility is due to lower income growth. The remainder is due to rising inequality. The mobility estimate is higher (78%) when income is adjusted (equivalised) for family size.
Keywords: D31; H00; J62; 330; intergenerational mobility; absolute mobility; Australia